Cross-border cooperation as an instrument of Europeanisation? Karelia ENPI CBC 2007-2013 and tourism cooperation - Zialian, Kristine (2015)
Implementation of the projects within Karelia ENPI CBC 2007-2013 has come to its end; however, the new programme under European Neighbourhood Instrument is to be launched in 2016. The research presents a study of Europeanisation of the Republic of Karelia through the programme of cross-border cooperation. External dimension of Europeanisation is studied in the context of a Russian region, the Republic of Karelia. Thus, Europeanisation is approached here as transfer of EU norms, values and practices to non-member countries. These principles of the EU are determined by analysis of documents on its policy towards neighbouring countries and present EU external governance. Activities of civil society organisations, mainly NGOs, within the programme contribute to cross-border cooperation. Cross-border cooperation and its programmes trigger activities and offer new opportunities for border regions, which to some extent contribute to Europeanisation through transfer of policy styles, norms and identities. It can partly be explained by the non-obligatory nature of policies within CBC in relation to civil society organisations in the border regions. Members of Russian NGOs involved into implementation of tourism projects were interviewed. Analysis of interviews contributed to gaining better understanding of potential adopting of European norms and practices through interaction and exchange of experience. In the research the necessity of the EU to europeanise neighbouring countries is explained as strengthening the EU position as a regional power and providing safety and stability near its border. In the Master s thesis I conclude that cross-border cooperation can be viewed as an instrument of Europeanisation but with the limitation of transfer of technological aspects of tourism development: logistics, managements rules, infrastructure, etc.